Monsoon Rainfall Variability in Large Excess Years - Bagale, Damodar; Aryal, Deepak (Perspectives on Higher Education, 2025)
The present study used 107 meteorological stations' rainfall time-series data from 1977 to 2018, over different physiographic regions of Nepal. The normal ratio method was adopted to fill in missing datasets. Monthly, seasonal, and annual data analyses were carried out for each site in Nepal. Non-parametric Mann-Kendall test identified monsoon rainfall decreasing by 0.36 mm/monsoon in the recent four decades. The east-west mid-mountainous range observed the heavy monsoon rainfall. The average monsoon rainfall is 1433.42 mm. The present study identified the seven large excess episodes. Out of them, four large excess episodes (1998, 1999, 2000, and 2007) are conceded with La Nina events which quantify significant excess rainfall (19.21, 12.07, 14.29, and 14.79) percent respectively from average rainfall. The western region experienced less rainfall than the eastern and central regions throughout the seven major monsoon excess years. The mid-mountainous of central Nepal has received more rainfall. At a 95% confidence level, the correlation coefficient between monsoon rainfall and the southern oscillation index (SOI) is 0.52.